Sasala nolani gen. n., sp. n. (Digenea: Aporocotylidae) from the body-cavity of the guineafowl puffer fish Arothron meleagris (Lacepède) (Tetraodontiformes: Tetraodontidae) from off Moorea, French Polynesia - Bray, Rodney A.; Cribb, Thomas H.; Littlewood, D. Timothy J. (Zootaxa, 2012)
The aporocotylid new genus and species Sasala nolani is described from the body-cavity of the guineafowl puffer fishArothron meleagris from off Moorea, French Polynesia. Sasala is distinguished by the combination of having an auxiliaryseminal vesicle, a tiny oral sucker, the single interand post-caecal testis, the post-ovarian uterus and the relatively shortposterior caeca. Sasala nolani ssrDNA and lsrDNA sequences have been used to infer its phylogenetic relationships withsome other aporocotylids, showing a particularly close relationship with ‘Paradeontocylix’ sinensis. A short comment onthe accumulation of eggs in the host gut wall is included, suggesting that the eggs remain in the gut wall after the adult worm infection is passed.